Excellent Service in Attracting and Retaining Customers at PT BPRS Al-Washliyah Medan - Ilaika Fauziah Abdi Hasibuan; Sri Ramadhani; Ahmad Syakir (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
Excellent service is a crucial step in attracting and retaining customers, where excellent service is providing the best service to customers in helping and meeting customer needs according to their expectations so that customers are satisfied and loyal. This article emphasizes the importance of excellent service, what services are provided by banks to attract and retain customers and what makes customers interested and stay at BPRS Al-Washliyah. This study uses a qualitative descriptive research method, namely conducting research by means of observation, interviews and other library sources in the form of books and journal publications. This study concludes that BPRS Al-Washliyah considers providing excellent service to customers very important in attracting and retaining customers and the bank applies the principle that customers are kings whose desires must be fulfilled as much as possible. BPRS Al-Washliyah offers superior products, provides pick-up services, and also provides rewards and conveniences that can make customers interested and stay as customers at BPRS Al-Washliyah.